Measuring Mitochondrial Substrate Flux in Recombinant Perfringolysin O-Permeabilized Cells - Elkalaf, Moustafa; Vaněčková, Karolína; Staňková, Pavla; Červinková, Zuzana; Polák, Jan; Kučera, Otto (Journal of visualized experiments, 2021)
Mitochondrial substrate flux is a distinguishing characteristic of each cell type, and changes in its components such as transporters, channels, or enzymes are involved in the pathogenesis of several diseases. Mitochondrial substrate flux can be studied using intact cells, permeabilized cells, or isolated mitochondria. Investigating intact cells encounters several problems due to simultaneous oxidation of different substrates. Besides, several cell types contain internal stores of different substrates that complicate results interpretation. Methods such as mitochondrial isolation or using permeabilizing agents are not easily reproducible. Isolating pure mitochondria with intact membranes in sufficient amounts from small samples is problematic. Using non-selective permeabilizers causes various degrees of unavoidable mitochondrial membrane damage. Recombinant perfringolysin O (rPFO) was offered as a more appropriate permeabilizer, thanks to its ability to selectively permeabilize plasma membrane without affecting mitochondrial integrity. When used in combination with microplate respirometry, it allows testing the flux of several mitochondrial substrates with enough replicates within one experiment while using a minimal number of cells. In this work, the protocol describes a method to compare mitochondrial substrate flux of two different cellular phenotypes or genotypes and can be customized to test various mitochondrial substrates or inhibitors.
Keywords: buněčné dýchání; spotřeba kyslíku; Bacterial Toxins; Mitochondria; Oxygen Consumption; Hemolysin Proteins; hemolyziny; mitochondrie; Cell Respiration; bakteriální toxiny